Analysis on Quality and Composition of Ink Pigments Used for Semi-permanent Makeup - Jin, Hyun-Sook; Chang, Byung-Soo (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Background/Objectives: This study selects some brown pigments manufactured by both local and foreign companies and analyzes their ultrastructural features and element compositions, in comparison of inorganic substance included in each pigment to define a possible problem and the cause after a semi-permanent makeup. Methods/Statistical analysis: A scanning electron microscope (SEM) is employed to see the form and microstructure of each pigment added to the local and foreign ink products selected, and an energy dispersive x-ray spectrometry (EDX) analyzes the element composition. Findings: The pigment from abroad is composed of iron (Fe) and titanium (Ti). The SEM tells it is made of iron oxide and titanium dioxide. The local ink consists of iron (Fe), manganese (Mn), silicon (Si), aluminum (Al), and sodium (Na). Observation on the SEM finds that characteristically there are a multiple micrometer-sized of polygonal flat substance and lots of impurities. Improvements/Applications: It is found that differences in homogeneity, roughness, and size of pigment particles are largely varied depending on whether the ink is expensive or not. It is considered that the pigment’s heterogeneity or an addition of contaminant, intentional or accidental, will have a big effect on customer satisfaction after a semi- permanent makeup procedure.